Immune Determinants in the Acquisition and Maintenance of Antibody to Hepatitis B Surface Antigen in Adults After First‐Time Hepatitis B Vaccination. Issue 6 (22nd April 2019) - Doi, Hiroyoshi; Yoshio, Sachiyo; Yoneyama, Keiichiro; Kawai, Hironari; Sakamoto, Yuzuru; Shimagaki, Tomonari; Aoki, Yoshihiko; Osawa, Yosuke; Yoshida, Hitoshi; Kanto, Tatsuya
Abstract : Global implementation of a birth‐dose hepatitis B (HB) vaccine has significantly reduced the prevalence of hepatitis B virus (HBV) carriers. Durable and sufficient titers of antibodies to hepatitis B surface antigen (anti‐HBs) are desirable for vaccinees to gain resistance to HBV exposure. However, the existence of primary nonresponders and vaccinees who lost anti‐HBs over time remains a challenge for the strategy of HBV elimination. We thus aim to clarify the mechanisms of acquisition and maintenance of vaccine‐induced anti‐HBs in healthy adults. We retrospectively analyzed the vaccination records of 3, 755 first‐time HB‐vaccinated students and also traced the acquired antibody transition of 392 first‐time vaccinees for 10 consecutive years. To understand the cellular and humoral immune response, we prospectively examined peripheral blood from 47 healthy first‐time HB‐vaccinated students, 62 booster‐vaccinated health care workers, and 20 individuals who maintained their anti‐HBs. In responders, a significant increase of follicular helper T (Tfh) cells, activated plasmablasts, and plasma cells was observed in first‐time‐vaccinated but not booster‐vaccinated persons. We also discovered memory B cells and antibody‐secreting cells were more abundant in individuals who maintained anti‐HBs. According to vaccination records, higher anti‐HBs antibody titer acquisition was related to the longer term maintenance of anti‐HBs, the level of which was positively correlated with prevaccination levels of serum interferon‐γ and related chemokines. The second series of vaccination as a booster provided significantly higher anti‐HBs antibody titers compared to the initial series. Conclusion : Coordinated activation of Tfh and B‐cell lineages after HB vaccination is involved in the acquisition and maintenance of anti‐HBs. Our findings support the rationale of preconditioning the immune status of recipients to ensure durable vaccine responses. Abstract : The acquisition of high titer at HB vaccination is important for the long‐term maintenance of anti‐HBs antibody. We demonstrated the vaccine‐induced anti‐HBs titer is influenced by the pre‐vaccination immune status of the recipient and conditioning the immunological milieu before vaccination can be a strategy to improve the impact of HB vaccination.